Risk assessment and management in violent extremism: a primer for mental health practitioners. Issue 3 (4th May 2021) - Logan, Caroline; Sellers, Rachel
ABSTRACT: This paper introduces a special issue of the Journal of Forensic Psychiatry and Psychology dedicated to violent extremism and mental health. We address three challenges faced by mental health practitioners who work with people whose harm potential may be ideologically motived. First, how can practitioners engage in good practice in risk assessment and management when the evidence base for such practice in the violent extremism field is limited? Second, how can a mental health practitioner establish and understand the role of an extremist ideology in a client in their care and differentiate it from motivational drivers that may result in broadly similar kinds of actual, attempted or threatened violence? Third, how can practitioners and their services respond to the risks posed in ways that recognise and balance the needs of both the client and those multiple other agencies dedicated to public protection? Following the examination of these challenges, and a brief comment about the relevance of coronavirus to risk of violent extremism, each paper in the special issue will be introduced and their contribution to the work of practitioners who carry such responsibility summarised. The paper concludes with key points and recommendations linked to the three challenges addressed.